ANALISIS DAMPAK PEMBIAYAAN BANK UMUM SYARIAH PADA PERKEMBANGAN USAHA MIKRO, KECIL DAN MENENGAH DI INDONESIA (MENGGUNAKAN ANALISIS VECTOR AUTO REGRESSION) - Imani, Safarinda Imani (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This research was conducted to find out what happened in banking and in Indonesia. This study uses the budget of sharia banking financial statements and the development of annual umkm 2006-2017 in Indonesia. By using stata 13. With long-term results, the financing of Sharia Commercial Banks and the development of MSMEs in Indonesia affect each other can be viewed on tabular trace statistics 5% critical value, that is financing of sharia banks 32,927 15,41, while the development of MSMEs in Indonesia ie 5.0362 3.76. Variable variables affect SMEs with F. Statistics F. Table, where the variable cost 0.000 1%, 5%, 10%, while the variable development of SMEs 0.001 1%, 5%, 10%, other variables that affect the financing of SMEs.